Nigeria and the Organization of Islamic Countries; 2004-2021 - Fadipe, Oluwakorede (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The study examines the fluctuating scope of the Nigeria Organisation of Islamic Countries (OIC) from 2004 to 2020, a time of increased complexities both from within and beyond Nigeria. The study relied on secondary sources such as journals and newsletters and adopted a qualitative method for indepth analysis. The findings of the study suggest that while the relationships can be beneficial to Nigeria, Nigeria’s political leaders must learn how to convey such an impression to its selective Christian community that it is not a ploy to convert Nigeria from secularism to an Islamic nation. Based on this, the study recommends that such scrutiny and skepticism towards Nigeria’s membership should be enlightened to objectively evaluate the OIC’s religious and socio-economic benefits, which Nigeria can take advantage of as a member.